Mader's understanding human anatomy & physiology - Susannah Nelson Longenbaker (New York, NY : McGraw-Hill Education, 2020)
Mader$1 (Bs Understanding Human Anatomy and Physiology continues to be the perfect text for a one-semester course, because it was designed for this audience from the very first edition. The text is celebrating its tenth anniversary with a complete facelift, which I believe makes the content even more approachable, user friendly and exciting. Each chapter now begins with an infographic that details fascinating facts about the chapter$1 (Bs subjects
Keywords: Human anatomy Textbooks; Physiology; Human physiology